Genetic Mechanisms of Y Chromosomal Microdeletions and Male Sterility: A Review - Oghenetega, Onome Bright; Innocent-Sunday, Onyinyechukwu Progress; Biibaloo, Legborsi Livinus; Obidinma, Chukwudifu Ebenezer; Kpai, Tonubari (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
Infertility is a disease of the male or female reproductive system defined by the failure to achieve a pregnancy after 12 months or more of regular unprotected sexual intercourse. The Y chromosome plays a major role in male fertility, as it contains genes responsible for testis development and the initiation and maintenance of spermatogenesis in adulthood. However, anomalies in these genes can cause male infertility. There are several ampliconic and palindromic sequences on the long arm of the Y chromosome (Yq), which makes it prone to self-recombination during spermatogenesis and thus susceptible to intra-chromosomal deletions. Y chromosome microdeletions are the second most common genetic cause of male infertility as it is present in about 5% and 10% of men suffering from oligospermia and azoospermia. The exact role of the genes affected by Y chromosome microdeletions in spermatogenesis is not fully understood. However, it is suggested that they play a critical role in germ cell development, particularly in males. Y chromosome microdeletions in infertile males typically occur within the three subregions of the long arm of the Y chromosome; azoospermia factor regions (AZF) a, b, and c. AZFa region genes support sperm cell production. AZFb region genes assist with the growth and maturity of sperm. AZFc genes do not contribute much to sperm production and hence deletions of the gene in this region, result in low sperm count. Microdeletion of AZFa genes leads to Sertoli cell-only syndrome, AZFb gene microdeletion can lead to maturation arrest and AZFc gene microdeletion can lead to hypospermatogenesis and azoospermia. This review aims to discuss in detail the effects and genetic underpinnings of Y chromosome microdeletions in male infertility.